Christian and Muslim Children and Adolescent Victims’ Armed Conflict Stress in Baloi and Kauswagan, Lanao del Norte, Mindanao - Estenzo Lim , Cora (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The study investigated the effects of cultural group, gender, and developmental stage on the Christian and Muslim children and adolescent victims’ experience of armed conflict stress. Utilizing a 2 x 2 x 2 factorial complete randomized design on 200 Christian and 200 Muslim children and adolescent victims of armed conflict, results showed that armed conflict stress was the general experience of all respondents. All main and interaction effects of the three variables cultural group, gender, and developmental stage significantly influenced the experience of stress among the respondents. Specifically, a significant 3-way interaction was shown in one significant interaction effect (stage and gender) among Christians and one significant main effect (stage) among Muslims. This means that among Christians, the effect of being a child or an adolescent on conflict stress varies depending on whether the child or adolescent victim is a male or a female. However, among Muslims, adolescents in general experience a higher conflict stress compared to children. Implications of the findings for the government, schools, the religious leaders, communities, and Filipino-Christian and Muslim families, are discussed.